Activity-Driven Dendritic Remodeling Requires Microtubule-Associated Protein 1A - Szebenyi, Györgyi (2005)
Activity-prompted dendritic remodeling leads to calcium-influx-dependent activation of signaling pathways within minutes and gene transcription within hours. However, dendrite growth continues for days and requires extension and stabilization of the cytoskeleton in nascent processes. In addition to binding microtubules, microtubule-associated proteins (MAPs) associate with the actin cytoskeleton, anchor ion channels and signaling complexes, and modulate synaptic growth. MAP2 is predominantly dendritic. MAP1B is at postsynaptic densities (PSD) and modulates ion channel activity, in addition to affecting axon growth. Less is known about MAP1A, but it is also enriched in dendrites at input locations, including PSDs where MAP1A associates with channel complexes and the calcium sensor caldendrin. MAP1A rescued hearing loss in tubby mice. Here we show that MAP1A becomes enriched in dendrites concurrently with dendritic branching and synapse formation in the developing brain; that synaptic activity is required for establishing mature MAP1A expression levels; and that MAP1A expression is required for activity-dependent growth, branching, and stabilization of the dendritic arbor.